Service Innovation Novel Ways of Creating Value in Actor Systems - Toivonen, Marja (Translational Systems Sciences, 2016)
This is the first book that summarizes the 20-year history of service innovation research and combines it with the future need to adopt a systems view in the field of service research. The book emphasizes that the most urgent issues of today's economies - the development of welfare and sustainability - cannot be solved with innovations in individual service offerings only, and that innovations of service systems are increasingly needed. Various theoretical approaches and perspectives from different disciplines are included, providing a comprehensive view of the current understanding of the nature of service innovation. The book illustrates the achievements of two research traditions, one based on the general innovation theory and the other based on the service marketing theory. Service innovation is considered from the points of view of drivers, processes, practices, and outcomes. The interrelations between actors and systems are analyzed, and the nature of innovation as a new way to co-create value is highlighted. The book promotes the view that users are an important source of innovative ideas and that openness is an important success factor in innovation processes. In addition to the general nature and management of service innovation, some specific topics are included, exemplified by innovations in public services and in knowledge-intensive business services. This volume is highly recommended to readers who seek a state-of-the-art overview of the area of service innovation and its linkages to systems research.